Assessing in vivo dynamics of multiple quality attributes from a therapeutic IgG4 monoclonal antibody circulating in cynomolgus monkey. Issue 5 (3rd July 2016) - Li, Yinyin; Huang, Yu; Ferrant, Janine; Lyubarskaya, Yelena; Zhang, Yue (Emma); Li, Siyang (Peter); Wu, Shiaw-Lin (Billy)
ABSTRACT: Characterization of biopharmaceutical proteins and assessment and understanding of the critical quality attributes (CQAs) is a significant part of biopharmaceutical product development and is routinely performed in vitro. In contrast, systematic analysis of the quality attributes in vivo is not as widespread, although metabolism and clearance of multiple variants of therapeutic proteins administered to non-human primates and human subjects may have a different impact on safety, efficacy and exposure. The major hurdles of such studies are usually sample availability and technical capability. In this study, we used affinity purification coupled with liquid chromatography and mass spectrometric analysis of the digested protein for consistent and simultaneous detection of the full amino acid sequence of a therapeutic IgG4 monoclonal antibody, MAB1. This methodology allowed us to assess in vivo changes of all sequence-related modifications and quality attributes of MAB1 over the duration of a preclinical pharmacokinetic study in cynomolgus monkeys.